2001
DOI: 10.1103/physrevlett.86.2439
|View full text |Cite
|
Sign up to set email alerts
|

Staggered Field Effect on the One-DimensionalS=12AntiferromagnetYb4

Abstract: Inelastic neutron scattering measurements of magnetic excitations in the charge-ordered state of Yb4As3 have been performed under magnetic field up to about 6 T. By applying a magnetic field, the spectrum at the one-dimensional wave vector q = 1 [ pi/d] changes drastically from a broad one corresponding to the spinon excitation continuum of the one-dimensional S = 1 / 2 spin system to a sharp one at a finite energy, indicating the opening of an energy gap in the system. The magnetic field dependence of the gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
69
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(79 citation statements)
references
References 15 publications
7
69
1
2
Order By: Relevance
“…Similar behavior has been observed in Cu-benzoate, 27-29 Yb4As3, 30 and KCuGaF6 31 and well explained by the presence of staggered Dzyaloshinskii-Moriya (DM) interactions. 32,33 We think that a similar mechanism applies to the present compound.…”
Section: Discussionsupporting
confidence: 52%
“…Similar behavior has been observed in Cu-benzoate, 27-29 Yb4As3, 30 and KCuGaF6 31 and well explained by the presence of staggered Dzyaloshinskii-Moriya (DM) interactions. 32,33 We think that a similar mechanism applies to the present compound.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, more attention has been paid to theoretical studies of exactly solvable quantum spin models involving nearest-, next-nearest-neighbor interactions, and multiple spin exchange models, etc [3][4][5][6][7][8][9][10]. Those models are closer to real quasi-one-dimensional magnets [11][12][13] comparing to standard ones with only nearest-neighbor couplings. Furthermore, it has been shown that quantum spin models can be simulated in artificial quantum system with controllable parameters.…”
mentioning
confidence: 99%
“…Recently some novel magnetic properties were discovered in a variety of quasi-one dimensional materials, such as copper benzoate Cu(C 6 D 5 COO) 2 3D 2 O[1, 2], Yb 4 As 3 [3,4,5] and BaCu 2 Si 2 O 7 [6]. In these materials, the Dzyaloshinskii-Moriya (DM) interaction [7,8,9] plays an important role, especially in an applied magnetic field.…”
mentioning
confidence: 99%
“…In particular, for metallic materials, e.g. Yb 4 As 3 [3], one could use external fields to modulate the magnetic transport properties which is one of the focal points for the spintronics.…”
mentioning
confidence: 99%